Pulse Oximetry Monitoring of Infants Who Require Prone Position For Sleep – Is There Evidence That This Practice Reduces SIDS? - Alcolado, Nicole; Hughes, David M. (DALHOUSIE MEDICAL JOURNAL, 2013)
At the IWK Health Centre infants with special medical or developmental needs who require prone and/or side-lying positions for sleep are currently monitored by pulse oximetry to presumably reduce the risk of SIDS. The aim of this paper was to determine if there is any evidence in the literature demonstrating that pulse oximetry monitoring of infants who sleep in the prone position has any effect on mortality from SIDS. A review of the literature was conducted and no studies were found that specifically address this question. Since medical practices should be based on evidence and there is currently none for this protocol, we believe it may be doing more harm than good.